Xylitol Production From Byproducts Generated During Sequential Acid-/Alkali-Pretreatment of Empty Palm Fruit Bunch Fiber by an Adapted Candida tropicalis - Kim, Seonghun (Frontiers in Energy Research, 2019)
Xylose is a pentose sugar with the potential to convert a variety of valuable chemical products. In this study, acidic pretreatment wastewater generated during a sequential acid-/alkali-pretreatment process was recycled to increase the hydrolyzed hemicellulose fraction from empty palm fruit bunch fiber (EPFBF), a lignocellulosic biomass. The xylose in the reused wastewater was subjected to overliming and an activated charcoal column was used to remove inhibitory compounds, for xylitol fermentation using the adapted C. tropicalis strain. The cell growth and xylose uptake rates in the adapted strain were 1.7- and 5-fold higher, respectively, compared to the wild-type strain. During batch fermentation using the adapted yeast strain and the post-pretreated xylose solution, 35.2 ± 0.8 g/L xylitol was obtained within 61 h for a production yield of 0.44 g xylitol/g xylose. These results indicate that xylose in the byproducts produced in the bioethanol process could be recovered for production of xylitol.